The experimental and computational determination of the deflection of welded T-beams - Bela, Sabo (Journal of Production Engineering, 1989)
The article discusses the evaluation of N.O. Okerbiom's method for calculating the deflection of welded I-beams and assesses the accuracy of this computational approach by comparing the calculated results with actual measurements.